Implementation of Water Level Measuring Instruments as Flood Indicator in the Rice Fields of Teluklada Village - Ceri Ahendyarti; Adi Nugraha; Imamul Muttakin; Ahmad Shulhany (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
Flooding in rice fields often occurs as a result of overflowing rainwater or overflowing river water. In addition, irrigation also often overflows and inundates farmers' fields. The way that is often done to overcome this is usually done every few minutes to the fields. An automatic tool is needed that can be used to be able to monitor water level activities that occur in rice fields. In that case farmers can make the best and timely decisions when rice fields will be flooded. The design process of this tool is carried out in 2 stages, namely the area analysis stage and the design of the tool design which will be carried out with the characteristics of rice fields in Teluklada village. The Water Level Measuring Tool as a Flood Indicator in Rice Fields is designed as a flood indicator by utilizing the HCSR04 sensor work function to detect water rise that occurs. Residents who received the notification message were surprised when they first received the flood warning message and felt helped by the presence of this water level measuring instrument because it can monitor rice fields remotely.